The importance of mammalian torpor for survival in a post-fire landscape - Stawski, Clare (Biol Lett, 2015)
Wildfires have increased in frequency and intensity worldwide with climate change as a main driving factor. While a number of studies have focused on population changes in regard to fires, there are essentially no quantitative data on behavioural and physiological adjustments that are vital for the persistence of individuals during and after fires. Here we show that brown antechinus, a small insectivorous marsupial mammal, (i) endured a prescribed fire in situ, (ii) remained in their scorched home range despite unburned areas nearby, and (iii) substantially increased post-fire torpor use and thus reduced foraging requirements and exposure to predators. Hence, torpor is a physiological adaptation that, although not quantified in this context previously, appears to play a key role in post-fire survival for this and other heterothermic species.